2018
DOI: 10.1021/acsomega.8b01983
|View full text |Cite
|
Sign up to set email alerts
|

Orthometalated N-(Benzophenoxazine)-o-aminophenol: Phenolato versus Phenoxyl States

Abstract: The molecular and electronic structures of the orthometalated ruthenium(III) and osmium(III) complexes of N -(benzophenoxazine)- o -aminophenol ( OX LH 2 ) that exhibits versatile redox activities are reported. The redox chemistry of OX LH 2 is remarkably different from that of N -(aryl)- o -aminophenol ( AP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…First, the Ag was immobilised onto the dressing via oxidation-driven polymerisation chemistry of PDA. Dopamine contains multifunctional groups of catechol and the amine rich proteins of marine mussels 24,27,28. It has been reported that DA possesses the ability to self-polymerise to form a nanometre thin coating on a wide range of substrates 18,29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the Ag was immobilised onto the dressing via oxidation-driven polymerisation chemistry of PDA. Dopamine contains multifunctional groups of catechol and the amine rich proteins of marine mussels 24,27,28. It has been reported that DA possesses the ability to self-polymerise to form a nanometre thin coating on a wide range of substrates 18,29.…”
Section: Discussionmentioning
confidence: 99%
“…The coating of the PDA and the deposition of the Ag were modified from process used in previous studies 14,18,24. Briefly, in step 1 (Ag coating), the CG samples (10 mm in length and 10 mm in width) were pre-wetted with a 0.1 M carbonate buffer (pH = 8.5) in a petri dish and covered completely before being placed under vacuum to remove trapped air bubbles.…”
Section: Methodsmentioning
confidence: 99%